Anthocyanin: a review of plant sources, extraction, stability, content determination and modifications. (21st October 2022) - Guo, Yuyan; Zhang, Huan; Shao, Shuang; Sun, Shuang; Yang, Dayu; Lv, Shaowa
Summary: Anthocyanins are flavonoids of the polyphenol family, which are secondary metabolites of natural products synthesised by blueberries, mulberry and other plants. As a natural edible pigment, it is not only plentiful, non‐toxic and safe, but also has high nutritional value and pharmacological effects. Several studies have shown that anthocyanins have many health benefits such as improving vision, promoting antioxidant activity, capturing free radicals and treating cancer in humans. They are becoming increasingly popular in the fields of food and medicine. However, in terms of their structures, natural anthocyanins are unstable, easily deteriorating under the influence of their own structures and external factors, which greatly limits their application. Therefore, it is particularly important to use appropriate extraction methods and techniques to enhance the stability of anthocyanins. This article summarises the current research on anthocyanins in terms of plant sources, extraction, stability, content determination and structural modifications, and provides a reference for improving their application in the fields of food and medicine. Abstract : Anthocyanins are typical nutrients, which are widely found in various fruits and vegetables and have rich nutritional and pharmacological values. However, it is very unstable and easy to be affected by external factors, which will lead to the content reduction. Therefore, it is essential to improve the stability of anthocyanins. Finally, it was found that structural modification could not only improve its stability, but also enhance its biological activity, which provided a strong guarantee for the wide application of anthocyanins.